Cadmium Oxide Nanoparticles Synthesis Using Pulsed Laser Ablation in a Liquid Medium and Investigation of their Antibacterial Activity - Riyam H. Shukur; Sulaiman M. Hasan (Frontiers in Biomedical Technologies)
Purpose: Recent years have witnessed a significant amount of research into laser ablation in liquids due to the many potential applications of laser microprocessing of materials, including the synthesis of nanomaterials and nanostructures. This study aims to explore the antibacterial effects of cadmium oxide on both positive and negative bacteria.